2021
DOI: 10.1097/hs9.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Therapies for the Treatment of Graft-versus-host Disease

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HCT) is a potentially curative therapy for patients suffering from hematological malignancies, and its therapeutic success is based on the graft-versus-leukemia (GvL) effect. Severe acute and chronic graft-versushost disease (GvHD) are life-threatening complications after allo-HCT. To date, most of the approved treatment strategies for GvHD rely on broadly immunosuppressive regimens, which limit the beneficial GvL effect by reducing the cytotoxicity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 101 publications
(264 reference statements)
0
12
0
Order By: Relevance
“…In addition to the GVHD treatments discussed above targeting specific T cell activation signals, cellular therapies for GVHD benefit from being able to target multiple pathways at once. Cellular therapies like Treg and mesenchymal stromal cell (MSC) were both studied in xenogeneic transplant models before moving into late stage clinical trials ( 134 , 135 ). While the suppressive mechanism(s) identified for each cellular therapy are distinct, one common theme is the secretion of anti-inflammatory cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the GVHD treatments discussed above targeting specific T cell activation signals, cellular therapies for GVHD benefit from being able to target multiple pathways at once. Cellular therapies like Treg and mesenchymal stromal cell (MSC) were both studied in xenogeneic transplant models before moving into late stage clinical trials ( 134 , 135 ). While the suppressive mechanism(s) identified for each cellular therapy are distinct, one common theme is the secretion of anti-inflammatory cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While the suppressive mechanism(s) identified for each cellular therapy are distinct, one common theme is the secretion of anti-inflammatory cytokines (e.g. IL-10, IL-35, TGF-β and PGE2) with only a limited role identified for inhibitory ligand/receptors ( 134 , 135 ). Phase I trials using these adoptive therapies have shown promising but mixed results, most likely due to the inefficiencies and irregularities involved with ex vivo expansion of these cells (NCT04678401) ( 136 ).…”
Section: Discussionmentioning
confidence: 99%
“…To meet this growing need to improve patient outcomes following allogeneic HSCT different approaches and new combinations of the above GVHD therapies continue to be investigated. Moreover, research continues to investigate a broad range of new therapeutics including, but not limited to, co-stimulatory blockade with abatacept (CD28 blockade), targeting cytokines using etanercept [tumour necrosis factor (TNF-α) blockade] and tocilizumab (IL-6R blockade), use of the kinase inhibitor ruxolitinib (JAK 1/2 inhibition) or the anti-proliferative reagent azacitidine (DNA-methyltransferase inhibition), glycoprotein targeting with sitagliptin (CD26/dipeptidyl peptidase-4 inhibition), and regulatory therapies including low dose IL-2 and transfer of Tregs [ 27 ].…”
Section: Allogeneic Haematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…Therefore, the targeting of CD26 in T cells has the potential to be useful in studies of GVHD. CD26 + T cells infiltrate the skin and intestinal tract in clinical GVHD, and these results strongly suggest that CD26 assists T-cell migration across the endothelial barrier, as well as a role for CD26 + T cells in the pathophysiology of GVHD [ 52 , 53 ]. In patients undergoing hematopoietic stem cell transplantation, gliptins are capable of attenuating a cleavage of Chemokine CXCL12, thus facilitating the homing and engraftment of donor cells.…”
Section: Cd26 Inhibitors In Acute Graft-versus-host Disease (Gvhd)mentioning
confidence: 99%